2020
DOI: 10.5713/ajas.18.0955
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of mineral elements in sheep grazing in the highland agro-ecosystem

Abstract: Objective: Minerals are one of the important nutrients for supporting the growth of sheep grazing in the highland, northwest of China. The experiment was conducted to investigate the relationship of both macro and micro minerals in sheep grazing in the highlands of six districts located in the Qilian Mountain of China. Methods: Samples of herbage (n = 240) and soil (n = 240) were collected at random in a "W" shape across the area designated for harvesting from 24 farms, where the sheep commonly graze in Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…These values were similar to those obtained for grasses (13.4 g kg −1 DM) and herbs (15.0 g kg −1 DM) and much lower than for legumes (31.6 g kg -1 DM) found in meadows of northern Europe [6]. P content in the sward (1.7-2.5 g kg −1 DM) obtained in the present work was similar to the average for the sward of meadows of Dynowskie Foothills SE Poland (2.1 g kg −1 DM) [7] and grass and legumes of Denmark meadows (2.5-2.7 g kg −1 DM), while lower than for meadow herbs of Denmark (3.4 g kg -1 DM) [6] and significantly higher than for mountain meadows of NE China (0.78 g kg −1 DM) [8]. Other studies have shown that P concentration in plants increases with increasing grazing intensity [39].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These values were similar to those obtained for grasses (13.4 g kg −1 DM) and herbs (15.0 g kg −1 DM) and much lower than for legumes (31.6 g kg -1 DM) found in meadows of northern Europe [6]. P content in the sward (1.7-2.5 g kg −1 DM) obtained in the present work was similar to the average for the sward of meadows of Dynowskie Foothills SE Poland (2.1 g kg −1 DM) [7] and grass and legumes of Denmark meadows (2.5-2.7 g kg −1 DM), while lower than for meadow herbs of Denmark (3.4 g kg -1 DM) [6] and significantly higher than for mountain meadows of NE China (0.78 g kg −1 DM) [8]. Other studies have shown that P concentration in plants increases with increasing grazing intensity [39].…”
Section: Discussionsupporting
confidence: 65%
“…K content (11.5-19.8 g kg −1 DM) obtained in the study was close to the average for the sward of Dynowskie Foothills meadow communities (16.0 g kg −1 DM) [7], lower than for grasses (24.7 g kg −1 DM), legumes (24.5 g kg −1 DM) and herbs (30.5 g kg −1 DM) of Denmark meadows [6] and much higher than for the mountain meadows of NE China (3.48 g kg −1 DM) [8]. Mg content (1.4-2.5 g kg −1 DM) obtained in the current study was similar to the average for the sward of Dynowskie Foothills meadow communities (2.3 g kg -1 DM) [7], higher than for grasses (1.3 g kg −1 DM), lower than for legumes (3.0 g kg −1 DM) and herbs (3.3 g kg −1 DM) of Denmark meadows [6] and similar in the lower range to mountain meadows of NE China (1.49 g kg -1 DM) [8]. Such differences in the content of elements in the sward of meadows of SE Poland, Denmark and mountain meadows of NE China may result from different climatic conditions, which are the mildest in Denmark and the harshest in the mountains of NE China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forage feeding can provide livestock most of its carbohydrate, fat, protein, vitamin, and mineral requirements (Suttle 2010). Mineral content in herbage is clearly linked to their concentration in the soil where plants have been grown and to the capacity of the different plant species to uptake and accumulate them into the edible parts (Fan et al 2020). Among the essential minerals for animals, most of them are required in so tiny amounts or are so abundant into soil that plants fulfill their requirements easily.…”
Section: Introductionmentioning
confidence: 99%